2009
DOI: 10.3945/ajcn.2008.27381
|View full text |Cite
|
Sign up to set email alerts
|

Lysine ingestion markedly attenuates the glucose response to ingested glucose without a change in insulin response

Abstract: Background: Ingested proteins are known to stimulate a rise in insulin and glucagon concentrations. In our effort to explain this effect, we have begun to measure the effect of individual amino acids. Objectives: The objectives were to determine the effect of lysine ingestion on insulin and glucagon concentrations and whether the effect is moderated by glucose ingestion. Design: Thirteen healthy subjects were studied on 4 occasions. Water, 25 g glucose, 1 mmol lysine/kg lean body mass, or lysine plus glucose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 17 publications
2
35
1
Order By: Relevance
“…4). This occurred even though the increase in that specific amino acid also was attenuated when ingested with glucose (17,26,30,31).…”
Section: Effect Of Ingestion Of Individual Amino Acids With Glucosementioning
confidence: 97%
See 1 more Smart Citation
“…4). This occurred even though the increase in that specific amino acid also was attenuated when ingested with glucose (17,26,30,31).…”
Section: Effect Of Ingestion Of Individual Amino Acids With Glucosementioning
confidence: 97%
“…The results for several of the amino acids have been published, that is, arginine (26), glycine (27), proline (17), phenylalanine (28), isoleucine (29), leucine (30), and lysine (31).…”
Section: Our Personal Observationsmentioning
confidence: 99%
“…We have previously investigated the impact of certain amino acids [24,25], and the present work focuses on lysine, tryptophan, arginine, proline and threonine. Lysine ingestion was reported to increase postprandial glucose clearance [26] and to stimulate the secretion of the gut hormones, CCK and GLP-1 [27]. Tryptophan is needed for the synthesis of serotonin, a neurotransmitter known to be involved in appetite regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability of Lysine to reduce the formation of glycated proteins in diabetes induced rats, have also shown to delay the appearance of the late pathologies associated with protein glycation [6]. Lysine is known to react with glucose with the glycated amino acid being excreted in urine and it has been shown to markedly attenuate the glucose response to ingested glucose without a change in insulin response in humans [7]. Furthermore, studies have shown that it reduces the formation of glycated proteins in diabetes induced animal models [5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been long known that diabetes is accompanied by hypozincemia [16] and hyperzincuria [17]. Animal studies showed that Zinc supplementation has improved fasting insulin level and fasting glucose in mice models [6,7]. In Korea 44 diabetic patients and 34 normal subjects were supplemented with 50 mg Zinc daily as Zinc gluconate for 4 weeks.…”
Section: Introductionmentioning
confidence: 99%